Effects of ABVD chemotherapy on ovarian function: epidemiology, hormonal dosages and ultrasound morphologic analyses in 270 patients with Hodgkin’s disease - Ciccarone, Mariavita; Cavaceppi, Paola; Tesei, Cristiano; Brunetti, Stefania; Pulsoni, Alessandro; Annibali, Ombretta; Gasparoli, Cristiano; Battistini, Roberta; Hohaus, Stefan; Pelliccia, Sabrina; Tafuri, Agostino; Cox, Maria Christina; et al. (Frontiers in Oncology, 2023)
Classical Hodgkin Lymphoma (HL) is a lymphoproliferative disease typically diagnosed in the young. The excellent results obtained with current treatment lead to long survival with age-related complications affecting patients’ survival and quality of life. One issue affecting HL patients is infertility. This problem can be easily overcome in males with seminal liquid cryopreservation, however, in females it is more complex either in terms of the quality of the cryopreserved material or the patients’ age at diagnosis. Moreover, not all chemo- or radio-therapies have the same negative impact on fertility. The main objectives of this study was to collect epidemiological information on HL patients involved in fertility preservation counseling and to analyze the impact of ABVD (adriamycin, bleomycin, vinblastine, and dacarbazine), the standard treatment for HL, on ovarian function, hormonal levels and ovarian and uterine tissue morphologies. Patterns of fertility preservation were also reported. Data were obtained from 270 female patients at HL onset who were interested in fertility counseling prior to therapy initiation. Each patient was assessed at HL diagnosis for levels of Anti-Mullerian Hormone (AMH), Follicle Stimulating Hormone (FSH), and 17β-oestradiol (17β-oe), with additional assessments at 6 and 12 months after chemotherapy. Patients were evaluated with ultrasound scans to study the number of ovarian follicles and the degree of uterine thickness at the same timepoints. The average patient AMH level showed a statistically significant reduction at 6 months after chemotherapy (p=0.05) and by the 12 month time point returned to near pre-chemotherapy values. FSH and 17β-oe levels did not significantly vary throughout the study period. ABVD chemotherapy was associated with a significant reduction of both ovarian follicles and endometrial thickness at the 6 month time point followed by a recovery at the 12 time point in both ovaries. Different results were observed when patients changed treatment to a more intensive one. Based on the results from the hormonal measurements and the follicle echography, it appears that the toxic effect of ABVD on fertility is transient, whereas, in contrast, more intensive therapies may potentially be more harmful and long-lasting.